Smart alloy metalized novel photonic NEMS photodiode with CuAlV/n-Si/Al junction structure - Karaduman, Oktay; Canbay, Canan Aksu; Dere, Aysegul; Orman, Yusuf; Al-Ghamdi, Ahmed A.; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2024)
In this work, a novel smart (shape memory) alloy metalized photonic silicon wafer photodiode with Schottky type CuAlV/n-Si/Al contact structure as a nano-electro-mechanical-system (NEMS) photodevice was fabricated by thermal evaporation technique. The CuAlV memory alloy used as the top Schottky metal contact electrode was produced by arc melting technique and a subsequent quenching in an iced-brine water medium, and its shape memory effect characteristics were revealed by thermal and structural tests. The fabricated photonic NEMS photodiode was characterized by different photo-electrical (I-V, I-t) and frequency/time dependent and illuminated capacitance (C-V/f, C-t, C-V/ill.) and conductance-voltage (G-V) measurements under different frequencies and artificial light intensity power conditions. The I-V tests showed an excellent current rectifying ability and very well net photocurrent generation features of the photodiode. The specific detectivity of the photodiode was found as high as almost approaching 1011 Jones. The SCLC (space charge limited current conduction) analyses made on the double-log I-V plots of the photodiode revealed that the trap-filling TFL-SCLC and trap-free SCLC current conduction mechanisms are the two prevailing conduction mechanisms in the forward bias voltage region. The density of interface states (Dit) of the fabricated photodiode was determined. Moreover, an excellent reproducibility of light-induced photocapacitance formation of the novel photodiode was demonstrated by C-V/t measurements under different artificial light power intensities.
Keywords: Cu-based SMA; NEMS schottky photodiode; detectivity; space charge limited current conduction (SCLC); photocapacitance; interface states